2016
DOI: 10.3171/2015.10.jns151544
|View full text |Cite
|
Sign up to set email alerts
|

Clipping of previously coiled cerebral aneurysms: efficacy, safety, and predictors in a cohort of 111 patients

Abstract: OBJECTIVE With the increasing number of aneurysms treated with endovascular coiling, more recurrences are being encountered. The aim of this study was to evaluate the efficacy and safety of microsurgical clipping in the treatment of recurrent, previously coiled cerebral aneurysms and to identify risk factors that can affect the outcomes of this procedure. METHODS One hundred eleven patients with recurrent aneurysms whose lesions were managed by surgical clipping between January 2002 and October 2014 were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…Previous research indicated that combined surgical and endovascular treatments may be safe and effective [18]. In a cohort study involving 111 patients who underwent clipping of previously coiled IA, 2.7% had major complications and underwent coil extraction as a result of post-operative stroke [26]. By contrast, we found that ischemic stroke was less frequent in the context of SAC or BAC as compared to surgical clipping alone among patients with unruptured IA.…”
Section: Discussioncontrasting
confidence: 48%
“…Previous research indicated that combined surgical and endovascular treatments may be safe and effective [18]. In a cohort study involving 111 patients who underwent clipping of previously coiled IA, 2.7% had major complications and underwent coil extraction as a result of post-operative stroke [26]. By contrast, we found that ischemic stroke was less frequent in the context of SAC or BAC as compared to surgical clipping alone among patients with unruptured IA.…”
Section: Discussioncontrasting
confidence: 48%
“…Additionally, 90% of patients had a good clinical outcome with modified Rankin Scale scores of 0-2. 4,15 Surgical clipping is a permanent solution in almost all cases, and, if aneurysm occlusion is verified by DSA, further recurrence is very rare. 14 Wallner et al reported a positive experience with the case of regrowth of a middle cerebral artery aneurysm that was initially occluded with a WEB device, recurred, and was re-treated with coiling.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similarly, in their cohort of 111 patients, Daou et al reported complete occlusion rates of 97.3% after re-treatment by clipping, indicating the safety and effectiveness of clipping as the re-treatment method after previous coiling. 4 Even if the procedure is safe and leads to high occlusion rates without increased complications, some aspects need to be considered before surgery. Coil extraction might be necessary in some cases to achieve complete aneurysm occlusion or better anatomical preparation due to profound scarring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, the majority of patients who underwent microsurgical clipping of a previously coiled aneurysm had "no change" or an "improved" outcome. 6,10,18,19,22,24,25,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Currently, the largest prospective series of subjects who underwent clipping of previously coiled aneurysms is the International Subarchnoid Aneurysm Trial (n=191), but it does not provide outcomes for this particular subset-group. 6 Although, this may be beneficial by having reduced surgeon expertise bias, it simultaneously 281 introduces risk for other confounding factors such as selection bias.…”
Section: Discussionmentioning
confidence: 99%